Meningkatkan Hasil Belajar Lompat Jauh Gaya Jongkok Melalui Modifikasi Media Pembelajaran Pada Siswa Kelas V SD Negeri Seruawan Kecamatan Kairatu - Tauran, Maryo; Hattu, Mesak (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2022)
Physical activity has an important role in schools, through physical activity students can be formed who are physically and mentally healthy and have high personality, discipline, sportsmanship which ultimately forms quality human beings. Based on the results of the author's observations at SDN Seruawan, Kairatu District, which describes the condition of the existence of physical education teachers in that school, namely that teachers only use existing facilities, in the process of learning activities such as the duration of the squat jump style, teachers only use baseboards as learning media before utilizing or using learning media that can support the achievement of the learning process such as cardboard, used motorbike tires, balloons, cones and raffia rope. From the results of pre-action observations carried out in July in the odd semester of the 2019/2020 academic year, students were not yet able to do long jump training well. The approach that can be taken to overcome problems in long jump learning is through modification of learning media. Teachers are stimulated to be able to create innovative forms of learning assisted by modifying learning media in the learning process in the form of Kasrdus media. Based on the empirical facts and theoretical facts above, the author is interested in conducting classroom action research with the title